2013
DOI: 10.1007/s10295-013-1238-x
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology for optimising the culture conditions for eicosapentaenoic acid production by marine bacteria

Abstract: Polyunsaturated fatty acids (PUFAs), especially eicosapentaenoic acid (EPA), are increasingly attracting scientific attention owing to their significant health-promoting role in the human body. However, the human body lacks the ability to produce them in vivo. The limitations associated with the current sources of ω-3 fatty acids from animal and plant sources have led to increased interest in microbial production. Bacterial isolate 717 was identified as a potential high EPA producer. As an important step in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…All the one-way ANOVA was performed using Origin 8 statistical package, while all the multi-way ANOVA was performed using Minitab 16 statistical software package (Elrazak et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All the one-way ANOVA was performed using Origin 8 statistical package, while all the multi-way ANOVA was performed using Minitab 16 statistical software package (Elrazak et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid ester group contains effective anti arthritic, anti-acne and anti-androgenic property. The alkene and hydrocarbons were essential for oil production have good antimicrobial activity (24)(25)(26)(27). Maheswari and Saraswathy reported that ethyl acetate extract of Bacillus derived alkene compounds possessed the pharmacological activity and also various Streptomycete and Actinoycete derived compounds showed the biological activity when compared to the plant derived phytochemicals (28).…”
Section: Discussionmentioning
confidence: 99%
“…Then, a subsequent response surface methodology (RSM) usually has to be applied to detect the optimum concentration values of each studied factor [13]. RSM was found to be effective in processes optimization for a vast number of industrial products including paints and coatings, foods and beverages, and pharmaceuticals [14]. RSM is able to capture the main effect of each factor and the interactions between them.…”
Section: Introductionmentioning
confidence: 99%